Evaluation of Novel Primers for Rapid Single-Step Detection of Pathogenic Leptospira spp. Using Duplex Polymerase Chain Reaction (PCR) Assay (Early view) - Noorizan Miswan, Nurlina Rosli, Nur Ain M. Hussin, Eugene Ong Boon Beng, Mohammad Ridhuan Mohd Ali, Siti Aminah Ahmed, Nabilah Ismail, Nurulhasanah Othman, Anizah binti Rahumatullah, G Veera Singham; Nyok-Sean Lau (Tropical Life Sciences Research, 2026)
Pathogenic Leptospira spp. infections are the cause of the endemic disease leptospirosis. The flu-like and febrile symptoms can deteriorate severely and become fatal if not treated with antibiotic therapy on time. However, the current gold standard diagnostic method being used, the microscopic agglutination test (MAT), can only detect antibodies approximately one week after the onset of symptoms, besides, it requires skilled personnel and live cultures. In this study, two primer sets targeting rrs and lipL32 genes were designed for simple, multiplex, and rapid molecular detection of Leptospira spp. The duplex PCR assay was evaluated using 15 Leptospira strains, comprising both pathogenic and non-pathogenic species, and demonstrated simultaneous detection and clear differentiation of pathogenic Leptospira spp. within a single PCR run. In a duplex PCR setting, the assay showed 100% sensitivity for both urine-spiked Leptospira interrogans serovar Copenhagenii and its gDNA, with a detection limit of 100 bacteria/mL for urine and 30 fg/uL for gDNA samples. The results were comparable to the adopted primers targeting lfb1 or secYIV genes in a singleplex PCR setting. The duplex PCR assay showed 100% specificity in detecting Leptospira spp. by amplifying the highly conserved rrs gene in Leptospira spp. and pathogenicity differentiation through the highly conserved lipoprotein encoding lipL32 gene in pathogenic strains. In contrast, the specificity of the singleplex PCR assay targeting lfb1 or secYIV genes for pathogenic strain differentiation was 89% and 78%, respectively.